A study on the relationship between attitudes towards sports and self-efficacy levels of individuals doing leisure time activities - Tapşın, Faik Orhun (2023)
The purpose of this study was to research the relationship between attitudes towards sports and self-efficacy levels of individuals who do leisure-time activities. 894 people voluntarily participated in our study. The personal information form, the attitude scale towards sports developed by Koçak (2014) and the general self-efficacy scale developed by Sherer, et al. (1982) and adapted to Turkish by Yıldırım and İlhan (2010) were used in the study. The data were analyzed in the SPSS 25.0 package software. Furthermore, statistical frequency analysis and reliability coefficient calculations were used and since the data were normally distributed, Independent Samples t-test was used for pairwise cluster comparisons and the Anova test was used for more than two comparisons. Analyses were conducted at a confidence interval of 95%. According to the results of the study, it was found that the total mean score of the participants' attitude towards sports (89.62) and the mean score of self-efficacy (60.08) were above the medium level. A positive and low-level significant relationship was found between the participants' general attitude towards sports (r= ,221), psychosocial development (r= ,215), physical development (r= ,206), mental development (r= ,123) and self-efficacy. As a result, it was found that the participants' self-efficacy level increased as the mean scores of the general attitude towards sports and the mean scores of the sub-dimensions increased.